2019
DOI: 10.1002/ece3.5070
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation phylogeography of the cockle Cerastoderma glaucum: Highly heterogeneous genetic differentiation in a lagoon species

Abstract: Aim Coastal lagoons form an intriguing example of fragmented marine habitats. Restricted gene flow among isolated populations of lagoon species may promote their genetic divergence and may thus provide a first step toward speciation. In the present study, the population genetic structure of the lagoon cockle Cerastoderma glaucum has been investigated to clarify the complex phylogeographic pattern found in previous studies, to localize major genetic breaks, and to discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 109 publications
2
6
1
Order By: Relevance
“…The English populations of A. viridis are therefore the result of a post-glacial recolonization. The differences observed between EngCh and the Mediterranean lineages could then be the result of a vicariance process, in line with what was described for the lagoon cockle Cerastoderma glaucum (Sromek et al 2019) or Cymodocea nodosa (Alberto et al 2008). This cleavage was also supported by the distribution of the symbiont assemblages (Tables 2 and S9).…”
Section: Vicariance Between the English Channel And Mediterranean Seasupporting
confidence: 84%
“…The English populations of A. viridis are therefore the result of a post-glacial recolonization. The differences observed between EngCh and the Mediterranean lineages could then be the result of a vicariance process, in line with what was described for the lagoon cockle Cerastoderma glaucum (Sromek et al 2019) or Cymodocea nodosa (Alberto et al 2008). This cleavage was also supported by the distribution of the symbiont assemblages (Tables 2 and S9).…”
Section: Vicariance Between the English Channel And Mediterranean Seasupporting
confidence: 84%
“…southeast Ireland and Wales) using a classical RADseq technique (Etter et al, 2011). Genetic diversity observed for C. edule in our study was similar to that reported for the sister species C. glaucum (He: 0.078 -0.137; Sromek et al, 2019); however, both cockle species showed lower genetic diversity at genomic scale than other bivalves such as Placopecten magellanicus (He = 0.271 ± 0.133, Van Wyngaarden et al, 2017), Crassostrea virginica (He ~ 0.300; Bernatchez et al, 2019), Ostrea edulis (He ~ 0.300; Vera et al, 2019) and Crassostrea gigas (He ~ 0.300; Gutierrez et al, 2017), suggesting the lower genetic diversity to be a particular feature of the genus Cerastoderma, although we cannot discard that the different methodologies applied for SNP genotyping in those studies might explain this observation.…”
Section: Genetic Diversitysupporting
confidence: 86%
“…A. tsao-ko gradually spread from the origin regions to the periphery through introduction. Generally, a higher genetic similarity is expected between neighboring populations than between distant ones for species with low dispersal ability (Sromek et al 2019 ; Wright 1943 ).…”
Section: Discussionmentioning
confidence: 99%